Navigating Sustainability in Malaysian Logistics: An Exploration of Operational Factors and Sustainable Logistics Performance - Danial, Muhammad Shafiq; Rahmat, Abdul Khabir (Advances in Social Sciences Research Journal, 2024)
As the global logistics industry undergoes a paradigm shift towards sustainability, this research investigates the intricate relationships between key operational dimensions and sustainable logistics performance within the context of the Malaysian logistics sector, with a focus on Selangor. The study adopts a cross-sectional research design and employs a stratified random sampling method to select 150 members from a list of 4,000 logistics service association members. A structured questionnaire, encompassing green customer relationships, sustainable transportation, eco-friendly warehouse operations, digital transformation initiatives, and sustainable logistics performance, is utilized to collect both quantitative and qualitative data. The study aims to analyze the data using multiple regression analysis to discern the statistical relationships between independent and dependent variables. This research not only contributes to the body of knowledge in sustainable logistics but also provides actionable insights for logistics professionals and policymakers in Selangor, guiding the industry towards a more sustainable and environmentally conscious future. The findings from this study is that Green Customer Relationship, Green Transportation and Green Operations positively impact the Sustainable Logistics Performance.